In vitro assessments predict that CYP3A4 contributes to a greater extent than CYP3A5 to prednisolone clearance. Issue 6 (24th September 2021) - Skauby, Ragnhild Heier; Bergan, Stein; Andersen, Anders M.; Vethe, Nils Tore; Christensen, Hege
Abstract: Because several steroid hormones are metabolized to their respective 6β‐hydroxy forms by CYP3A4 and CYP3A5, these isoenzymes have been assumed to metabolize the immunosuppressive drug prednisolone, with conflicting results in the literature with respect to their relative importance. A direct study of the metabolism of prednisolone by microsomal CYP3A4 and CYP3A5 is missing. The aim of this in vitro study was to investigate the relative importance of recombinant CYP3A4 and recombinant CYP3A5 in the metabolism of prednisolone and to compare the extent of formation of 6β‐OH‐prednisolone by the two enzymes. Through in vitro incubations using rCYP3A4 and rCYP3A5 enzymes, intrinsic clearance (CLint ) of prednisolone was determined by the substrate depletion approach. Formation of the metabolite 6β‐OH‐prednisolone by rCYP3A4 and rCYP3A5, respectively, was compared. Prednisolone concentrations were measured, and its metabolite 6β‐OH‐prednisolone was identified using a HPLC‐MS/MS in‐house method. CLint for prednisolone by rCYP3A5 was less than 26% relative to rCYP3A4. Formation of 6β‐OH‐prednisolone by rCYP3A5 was less than 11% relative to rCYP3A4. The study indicates that 6β‐hydroxylation of prednisolone assessed in vitro in recombinant CYP enzymes depends on rCYP3A4 rather than rCYP3A5 and that CYP3A5 may be responsible for the formation of other prednisolone metabolite(s) in addition to 6β‐OH‐prednisolone.